CHANGES IN THE ORAL MUCOSA IN PREGNANT WOMEN - Toshtemirova Mohira Mahmud qizi; Xudoyberdiyeva Xumora Hasanovna (Journals Park Publishing, 2023)
It has been suggested about changes in the oral mucosa in pregnant women.
Keywords: Oral mucosa, modern dentistry, infection focus, preventive property.